Determinants of Fiscal Stress on Local Government Finances in East Java - Sofia Septi Suryani; Windijarto Windijarto (International Journal Labs, 2023)
The growing demands for public services have an impact on the availability of funds to meet these demands. This condition caused budgetary pressure on the government which was later called fiscal stress. This study aims to determine the factors that cause fiscal stress as seen from the financial statements of local governments in East Java. The analysis method used in this study is the Data Regression Panel, which is a combination of cross-section and time series data. The population and samples used are regencies/cities in East Java. This research resulted in the discovery that Regional Original Income (PAD), Equalization Fund (DP), Employee Expenditure (BP), Goods and Services Expenditure (BBJ), and Surplus/Deficit (PM) had a significant effect on Fiscal Stress. This result can be used as a consideration for the regency/city government in East Java to carry out good management of the performance activities of the District/city government by taking into account internal factors, namely Regional Original Income, Balance Fund, Expenditure, surplus/deficit, and budget absorption so that the regency/city government can avoid fiscal stress.